A Preliminary Investigation on Serious Mortalities of Fish in Balikligol (Halil-Ur Rahman Golu, Sanliurfa) - Oktener, Ahmet; Egribas, Erkan; Basusta, Nuri (Gazi Univ, 2008)
This investigation was conducted in July 2005 when dead fish were encountered in Balikligol. A parasitic copepod, Lamproglena pulchella Nordmann, 1832 (Cyclopoida; Lernaeidae) in the gills of two cyprinid species was reported for the first time in Balikligol (Sanliurfa). The Infestation prevalence was 100 % on both Cyprinus carpio and Capoeta trutta. The mean intensity of infection was 7.2 individuals on Cyprinus carpio and 6.3 on Capoeta trutta. Intensity minimum-maximum on Cyprinus carpio and Capoeta trutta respectively was 4-16; 6-13. The aim of this work is to draw attention to the occurrence of Lamproglena pulchella with the poor environmental factors in Balikligol which may be responsible for the cases of fish mortalities and the secondary infections which are emphasized in this work; and its use as a biomonitor species to evaluate the pollution and the biological quality of aquatic habitat.
Keywords: Fish mortality; Balikligol; pollution; biomonitor; Lamproglena; Cyprinus; Capoeta